Analitično spremljanje razvoja elastoplastičnega stanja med upogibom nosilcev pravokotnega prereza - Halilovič, Miroslav (Strojniški vestnik, 2007)
The deflection analysis of beams with rectangular cross-sections is consideredunder specific loading conditions and assuming elasto-plastic behaviour with no hardening. Within the framework of the small-strain and small-displacement approach, analytical solutions are derived that enable the elasto-plastic analyses of beams to be performed in a closed analytical form. As a consequence, clear tracing of the evolution of the elasto-plastic response with a propagation of the plastic zone through the solid body, i.e., its spreading along the beamćs longitudinal axis as well as its penetration through the cross-section, is enabled as loads increase, from the appearance of a first plastic yielding in the structure until its collapse.
Keywords: nosilci; elastoplastična deformacija; elastoplastična analize; analitične funkcije